Bioinformatic screening for key miRNAs and genes associated with myocardial infarction. Issue 6 (19th April 2018) - Wu, Ke; Zhao, Qiang; Li, Zhengmei; Li, Nannan; Xiao, Qiang; Li, Xiuchang; Zhao, Quanming
Abstract : Despite significant advances in understanding of the causes of and treatment of myocardial infarction (MI) in recent years, morbidity and mortality is still high. The aim of this study was to identify miRNA and genes potentially associated with MI. mRNA and miRNA expression datasets were downloaded from the Gene Expression Omnibus database (http://www.ncbi.nlm.nih.gov/geo/ ). Interactions between miRNA and the expression and function of target genes were analyzed, and a protein–protein interaction network was constructed. The diagnostic value of identified miRNA and genes was assessed. Quantitative RT‐PCR was applied to validate the results of the bioinformatics analysis. MiR‐27a, miR‐31*, miR‐1291, miR‐139‐5p, miR‐204, miR‐375, and target genes including CX3CR1, HSPA6, and TPM3 had potential diagnostic value. The genes TFEB, IRS2, GRB2, FASLG, LIMS1, CX3CR1, HSPA6, TPM3, LAT2, CEBPD, AQP9, and MAPKAPK2 were associated with recovery from MI. In conclusion, the identified miRNA and genes might be associated with the pathology of MI. Abstract : Treatment of myocardial infarction (MI) has improved in recent years, but morbidity and mortality is still high. In this study, we used bioinformatics techniques to identify miRNA and genes potentially associated with MI, validating these results by quantitative RT‐PCR. A group of miRNA and genes had potential diagnostic value, while another group of genes was associated with disease recovery. These identified miRNA and genes might be associated with the pathology of MI.